H2-Histamine antagonist (Famotidine) induced adverse CNS reactions with long-standing secondary mania and epileptic seizures - Einsiedel, Regina W. von; Roesch-Ely, Daniela; Diebold, Klaus; Sartor, Klaus; Mundt, Christoph; Bergemann, Niels (Pharmacopsychiatry, 2002)
Thieme E-Books & E-Journals
Gesehen am 15.12.2020